The Education of School Cultural Values to Increase the Students’ Character Values of the Muhammadiyah School in the Pandemic covid 19 Era - Sutarman Sutarman; Yusutria Yusutria (Universitas Muhammadiyah Ponorogo, 2021)
The purpose of this study was to find out in-depth the education pattern of school cultural values to increase the students’ character values of Muhammadiyah School in Bangunjiwo Kasihan Bantul of the Covid 19 Pandemic era. This research is qualitative research with a qualitative descriptive approach. The results of this research showed that: The Pattern of School Cultural Education in School of Muhammadiyah in Bangunjiwo Kasihan Bantul Yogyakarta of the Covid 19 pandemic era covers: (1) Reading Culture the Qur'an and general science; (2) Dhuha qiyamul lail prayer; (3) Praying of Jama'ah, Dhuhur, and Asar to train students regularly in congregation in a mosque around the school or the students’ home that it becomes a habit. (4) Smile, Greetings, Greetings, Polite and Polite Habits, (5) fasting (Sunnah Monday-Thursday or fasting the obligatory Ramadhan. After obtaining a regular school culture, students got the transformation of character values, namely: (1) the culture of reading Al-Qur'an sharpens faith and faith as well as general science which is useful for increasing religious values and scientific insight; (2) Dhuha prayer, the obligatory prayer 5 times in congregation and tahajud prayer increased the value of faith and piety; (3) fasting (Sunnah Monday-Thursday or fasting the obligatory Ramadhan increased the value of faith, morals, and self-control.